Fatigue life prediction of casing welded pipes by using the extended finite element method (Fracture and Structural Integrity, 2016)
The extended finite element (XFEM) method has been used to simulate fatigue crack growth in casing pipe, made of API J55 steel by high-frequency welding, in order estimate its structural integrity and life. Based on the critical value of stress intensity factor KIc, measured in different regions of welded joint, the crack was located in the base metal as the region with the lowest resistance to crack initiation and propagation. The XFEM was first applied to the 3 point bending specimens to verify numerical results with the experimental ones. After successful verification, the XFEM was used to simulate fatigue crack growth, position axially in the pipe, and estimate its remaining life.
Keywords: XFEM; Seam casing pipes; Axial surface crack; Fatigue crack growth; Remaining life.